Effect of foliar application of gibberellic acid on different growth contributing characters of mungbean (Progressive Agriculture, 2018)
The comparative growth and yield performances between two Mungbean (BARI Mung 6 and BARI Mung 5) varieties with foliar application of GA3 (0, 50, 100 and 150 ppm) were studied to find out the suitable variety and optimum level of GA3 application. The design of experiment followed was RCBD. Data on morpho-physiological characteristics were recorded at 15, 25, 35, 45and 55 days after sowing (DAS) and yield contributing parameters were recorded only at harvest stage. The results showed that application of GA3 @ 100 ppm produced better performance on morpho-physiological characters namely, plant height (56.59cm), number of leaves per plant (10.75), branches per plant (4.75), length of root (24.73cm), total dry matter weight (12.67g)which were recorded from the variety BARI mung 6 with the foliar application of GA3 @ 100 ppm. Yield contributing characters were also showed the highest performance in terms of number of pods per plant (23.40), pod length (6.67cm), number of seeds per pod (12.82), thousand seed weight (33.95 g), seed yield (7.53 g/plant and 1.92 t ha–1), and harvest index (35.36%) which were the highest with the application of 100 ppm GA3 in case of BARI Mung 6. Single and combined effects of treatments were found statistically significant. Between two varieties BARI Mung 6, among the treatments GA3 @ 100 ppm as foliar application and interaction effect of GA3 @ 100 ppm and BARI mung 6 showed the highest performance in respect of all growth and yield parameters.Progressive Agriculture 29 (3): 233-238, 2018